Profiles of Work Engagement and Work-Related Effort and Reward Among Teachers: Associations to Occupational Well-Being and Leader–Follower Relationship During the COVID-19 Pandemic - Pöysä, Sanni; Pakarinen, Eija; Lerkkanen, Marja-Kristiina (Frontiers in Psychology, 2022)
This study examined teachers’ occupational well-being by identifying profiles based on teachers’ self-ratings of work engagement as well as work-related effort and reward. It also did so by examining whether the identified subgroups differed with respect to teachers’ self-reported occupational stress and emotional exhaustion as well as with respect to work-related resources such as the individual resource of work meaningfulness and the leader-level resource of the leader–follower relationship. The participants in the study were 321 Finnish elementary school teachers. The data were collected in spring 2021, that is, at the time when the COVID-19 pandemic was present, yet there were no national school closures. Three groups of teachers were identified with latent profile analysis: 1) teachers recognized as being poorly engaged with the highest effort and lowest reward (4.7%); 2) teachers recognized as being averagely engaged with higher effort than reward (32.1%); and 3) teachers recognized as being highly engaged with higher reward than effort (63.2%). The subsequent analyses examining the differences among the profile groups revealed, for example, that each profile group differed with respect to the individual resource of work meaningfulness and Profile groups 2 and 3 differed with respect to the leader-level resource of the leader–follower relationship. Thus, the findings indicate that there are differences in the ways in which teachers are able to benefit from the work-related resources and how they cope with job-related demands during the COVID-19 pandemic.